Internalisasi Nilai-Nilai Religius dalam Membentuk Karakter Siswa - Suwarni Suwarni (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2021)
The internalization of character values ​​in the learning process in schools is still a problem, because it is seen as not being able to form religious characters. The number of problems such as students involved in brawls, criminal acts, disturbing friends, lack of concern for the environment, and lack of courtesy to teachers. So it is necessary to internalize religious values, one of which is related to the formation of religious attitudes. Students have a strong caring spirit and can carry out what religion has ordered. This study aims to analyze the strategy of internalizing religious values ​​at MTs Munawaroh. There are two things that are the focus of the research, namely (1) religious values ​​developed in PAI learning, (2) strategies for internalizing religious values ​​in PAI learning. This research uses a qualitative approach with descriptive qualitative research. Data collection techniques by observation, interviews, and documentation. Data analysis techniques with data reduction, display them to draw conclusions. As for checking the validity of the data using data triangulation which includes triangulation of data sources and triangulation of methods. The results of this study are (1) the religious values ​​developed at MTs Munawaroh, namely faith, taqwa, sincerity and patience. (2) The strategy for internalizing religious values ​​by MTs Munawaroh is introduction, appreciation, deepening, habituation and experience.